Evaluation of measurement equivalence of the Family Satisfaction with the End-of-Life Care (FAMCARE): Tests of differential item functioning between Hispanic and Non-Hispanic White caregivers - Teresi, Jeanne A. (Palliat Support Care, 2020)
OBJECTIVES. Although the psychometric properties of the Family Satisfaction with End-of-Life Care measure have been examined in diverse settings internationally; little evidence exists regarding measurement equivalence in Hispanic caregivers. The aim was to examine the psychometric properties of a short-form of the FAMCARE in Hispanics using latent variable models and place information on differential item functioning in an existing family satisfaction item bank. METHODS. The graded form of the item response theory model was used for the analyses of differential item functioning; sensitivity analyses were performed using a latent variable logistic regression approach. Exploratory and confirmatory factor analyses to examine dimensionality were performed within each subgroup studied. The sample included 1,834 respondents: 317 Hispanic and 1,517 non-Hispanic White caregivers of patients with Alzheimer’s disease and cancer, respectively. RESULTS. There was strong support for essential unidimensionality for both Hispanic and non-Hispanic White subgroups. Modest differential item functioning of low magnitude and impact was observed; flagged items related to information sharing. Only 1 item was flagged with significant differential item functioning by both a primary and sensitivity method after correction for multiple comparisons: “The way the family is included in treatment and care decisions”. This item was more discriminating for the non-Hispanic, White responders than for the Hispanic subsample, and was also a more severe indicator at some levels of the trait; the Hispanic respondents located at higher satisfaction levels were more likely than White non-Hispanic respondents to report satisfaction. SIGNIFICANCE OF RESULTS. The magnitude of differential item functioning was below the salience threshold for all items. Evidence supported the measurement equivalence and use for cross-cultural comparisons of the short-form FAMCARE among Hispanic caregivers, including those interviewed in Spanish.